Improving the Performance of the Tulungagung Police Satbinmas in Preventing the Crime of Theft - Manurung, Juan Putra (Police Studies Review, 2024)
The rise in incidents of theft occurring in the jurisdiction of the Tulungagung Police is a disruption to security and social order which is very disturbing to the community. The police, who are community protectors, are obliged to maintain security and social order. Through the Community Development Unit, Police can take preventive and pre-emptive measures in dealing with criminal acts of theft. The approach in this research is a qualitative approach with a type of field research with collecting primary and secondary data from related agencies through interviews, observations and document studies combined with validation techniques from data triangulation. The results of this research found that cases of criminal acts of theft have increased. Therefore, it is necessary to improve the performance of the Community Development Unit in preventing criminal acts of theft. The efforts made are to carry out a series of proactive and innovative efforts to prevent cases of theft with an approach that focuses on involvement and cooperation with the community and agencies.